Bruch's Membrane Opening Minimum Rim Width Measurement with SD-OCT: A Method to Correct for the Opening Size of Bruch's Membrane. (2nd October 2017) - Kromer, Robert; Spitzer, Martin Stephan
Abstract : A precise evaluation of the retinal nerve fiber layer thickness (RNFLT) is key for diagnosing and monitoring glaucoma. The Bruch's membrane opening minimum rim width (BMO-MRW) has been proposed as a reproducible assessment of the optic nerve. The BMO-MRW measures the minimum distance from the BMO to the internal limiting membrane. We propose an approach to correct the BMO-MRW using the BMO size for increased accuracy in interindividual comparisons in future studies. Eighty-one healthy patients received SPECTRALIS spectral domain optical coherence tomography measurements for the peripapillary RNFLT and BMO-MRW. We calculated a BMO size-corrected BMO-MRW using the mean BMO size of our cohort. BMO size was defined using the manufacturer-provided BMO area and manually measured BMO perimeter. We observed that the BMO-MRW correlated highly with the perimeter (r = − 0.553, p < 0.0001 ) and the area of the BMO (r = − 0.546, p < 0.0001 ). Using these parameters, we provided a corrected BMO size-adjusted BMO-MRW which was better correlated with the RNFLT compared to the noncorrected one (z = − 3.3495, p = 0.0004 ). We demonstrated the dependency of the BMO-MRW on ONH size. Furthermore, we showed the superiority of the corrected BMO-MRW using either the manually measured optic nerve head perimeter or the automatically provided ONH for future studies.